P.074 Infantile idiopathic intracranial hypertension - a case study and review of the literature. (June 2019) - Boles, S; Tibussek, D; Pohl, D
Abstract : Background: Idiopathic intracranial hypertension (IIH), or pseudotumor cerebri, is an increase in intracranial pressure due to unknown etiology. Presentation in infancy is extremely rare. Little is known about infantile IIH and age-specific treatment guidelines are lacking. Methods: Patient data was obtained from medical records at the Children's Hospital of Eastern Ontario. A literature review of infantile IIH was performed. Results: A previously healthy 9-month-old boy presented with irritability, decreased appetite, and a bulging fontanelle. CT head imaging and cerebrospinal fluid studies revealed normal results. Symptoms transiently resolved after a lumbar puncture, but 11 days later, his fontanelle bulged again. A second lumbar puncture revealed an elevated opening pressure of 35 cm H2O and led to a diagnosis of IIH in accordance with the modified Dandy Criteria. Treatment with acetazolamide at a dose of 25 mg/kg/day was initiated and the patient remained symptom-free for 6 weeks, followed by another relapse. His acetazolamide was increased to 38 mg/kg/day, with no further relapses to date. Conclusions: A diagnosis of IIH is challenging in infants, since the patients cannot yet verbalize typical IIH-related symptoms, and papilledema is difficult to assess. If undetected and untreated, IIH may result in permanent visual deficits.